Alternative growth scenarios for Ugandan coffee to 2020 - You, Liangzhi; Bolwig, Simon (International Food Policy Research Institute, 2003)
Coffee is the most important export crop in Uganda and an important source of income among smallholder farmers in large parts of the country. The Robusta type dominates coffee production and Ugandan Robusta is demanded by roasters as a component in certain blends due to its special taste qualities. However, a combination of events outside and within Uganda, especially the collapse of world coffee prices in the late 1990s, are eroding farmer incomes and export revenues and threaten the long-term viability of the industry. In this context, the paper first investigates the challenges faced by the Ugandan coffee industry, namely the decline in the world coffee market, changes in procurement strategies among coffee importers, the rapidly expanding market for high quality and specialty coffees, and the spread of the coffee wilt disease and other farm-level productivity constraints. This leads us to examine possible development strategies for Ugandan coffee production: area expansion, quality improvement, and productivity increase. Using IFPRI’s Dynamic Research Evaluation for Management (DREAM) model, different scenarios for each of these strategies are evaluated to show their potential impacts on Ugandan export prices, export revenues, and producer benefits. The simulation results show that Uganda would benefit relatively more by enhancing farm productivity and improving coffee quality. The economic benefits of increasing production through area expansion, on the other hand, would be significantly eroded by the negative effects on export prices, especially if other countries followed suit and accelerated their own growth in coffee production. These analyses focus on the potential benefits of alternate changes in Ugandan coffee production, while devoting less attention to how and at what costs such changes may be effected. Finally, it is suggested that because the world coffee market is so important to the Ugandan economy, and being the third biggest Robusta producer in the world, Uganda has a high stake and important role to play in international coordination efforts to raise and stabilize world coffee prices.